PENGARUH RASIO KEUANGAN TERHADAP KINERJA KEUANGAN BANK SYARIAH (Studi pada Bank Umum Syariah yang Terdaftar di Otoritas Jasa Keuangan Republik Indonesia Tahun 2014-2016) - Priska Trias Agustin; Ari Darmawan (Jurnal Administrasi Bisnis, 2018)
This research was conducted to discover the variable of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Efficiency Ratio (OER), and Financing to Deposit Ratio (FDR) about Return On Assets (ROA). The type of research that used in this research is explanatory research, with a quantitative approach. The data used in this research is secondary data, using quarterly data during the period of January 2014 until December 2016, the number of data obtained is 132 (4 periods per year X 11 bank X 3 years). Multiple linear regression of analysis. The result of this research is correlation coefficient value (R2) for 0,675. Relevant variable of dependent variable about 67,5% and the rest which is 32,5% affected by the other variable beyond this research. The test result of F shows that the variable of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Efficiency Ratio (OER), and Financing to Deposit Ratio (FDR) simultaneously have significant effect on Return On Assets. Kеywords: CAR, NPF, OER, FDR, ROA АBSTRАK Penelitian ini dilakukan bertujuan untuk mengetahui pengaruh Capital Adequacy Ratio (CAR), Non Perfroming Financing (NPF), Operational Efficiency Ratio (OER), dan Financing to Deposit Ratio (FDR) terhadap Return On Assets (ROA). Jenis penelitian yang digunakan adalah explanatory research, dengan pendekatan kuantitatif. Data yang digunakan adalah data sekunder, dengan menggunakan data perkuartal selama periode Januari 2014- Desember 2016, sehingga diperoleh jumlah data adalah sebanyak 132 (4 periode kuartal pertahun X 11 bank X 3 tahun). Analisis yang digunakan adalah analisis regresi linier berganda. Hasil dari penelitian ini diketahui bahwa nilai koefisisen determinasi (R2) sebesar 0,675 yang berarti variabel independen mempengaruhi variabel dependen sebesar 67,5% dan sisanya yaitu 32,5 dipengaruhi oleh variabel lain diluar penelitian ini. Hasil uji F menunjukkan bahwa variabel independen Capital Adequacy Ratio (CAR), Non Perfroming Financing (NPF), Operational Efficiency Ratio (OER), dan Financing to Deposit Ratio (FDR) secara simultan berpengaruh signifikan terhadap Return On Assets (ROA). Kаtа Kunci: CAR, NPF, OER, FDR, ROA